(3cJGH GdZUHs - (3GdajVj, CMeO Hf eMeO eMSf, J (B1290(3g`s ((3eMeO Ydj Hf Ndjd GdNhfSGQjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3GdHGH GdKGfj aj PcQ HGbj CSHGH GdVeGf GdeJYGQa(B...s
(3BNQgG (B:s
(3hPdc deG bQQfG aj ChGFd GdcJGH Cf GdMQ dG jONd JMJ GdjO hdG jJYdb Hg ZUH(B... (3hdG THgI JYJQjg(B. (3hGddg gh GdYGde(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B1(3, U(B236s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3abg GdePGgH GdCNQis